Yield, Productivity and Economics of Integrated Farming System under Irrigated Conditions of Western Maharashtra - P. P. Kharche; U. S. Surve; P. A. Mahadule; S. B. Salgar; S. C. Patil (Research Highlights in Agricultural Sciences Vol. 1, 2022)
The study was conducted at All India Co-ordinated Research Project on Integrated Farming System, Mahatma Phule Krishi Vidyapeeth, Rahuri during 2018-2019 and 2019-2020 to develop integrated farming system model for irrigated conditions of Western Maharashtra. The model was designed for 1 ha area with crop, horticulture, dairy, goat, poultry and vermicompost unit. The integrated farming system model generated sugarcane equivalent yield of 375 t ha-1. The gross monetary returns from crop + horticulture + dairy + goat + poultry + vermicompost unit were 10,55,758 and net monetary returns of 4, 58, 943 with B:C ratio (1.77). Of this total net returns obtained from integrated farming system model per cent contribution of different components were crop (25%), horticulture (4%), dairy (24%), goat (18%), poultry (29%) and vermicompost (7%). Employment generation in integrated farming system model was 422 Man days year-1.